(untitled) (Research, Society and Development, 2023)
The present research aims to present the environmental compensation resulting from intervention in APP, provided for in CONAMA Resolution nº 369, of 2006, in a quarry located in the municipality of São Thomé das Letras, MG, demonstrating its importance for the controlled exploration, of way to ensure that economic development tries to go hand in hand with maintaining the quality of the environment. The methodology used to develop this research was the case study, which had a theoretical basis through research in technical articles, reports, master’s dissertations, doctoral theses, together with available literature. Carrying out compensatory measures means that socioeconomic development goes hand in hand with the preservation of the environment, as long as everyone involved does their part, guaranteeing employment and income for quarry employees, as mining activity is the main source of these resources in the municipality. In this way, environmental compensation can act as a way of reconciling socioeconomic development with ecological preservation, operating as an instrument for sustainable development. But for this to happen, it is essential that there is an economic-environmental balance, where compensation measures are not established that make truly necessary projects unfeasible and where the development of activities with great potential for degradation are not allowed, even when accompanied by environmental compensation. Despite the desired advances, the ideal of having a cohesive system remains far from happening and much still needs to be done to ensure compliance with legislation and due oversight.